BRAINSTORMING TECHNIQUE TO IMPROVE WRITING SKILL IN DESCRIPTIVE TEXTS OF VOCATIONAL HIGH SCHOOL STUDENTS - Candra Minawati (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2018)
The article was based on a research that concerned in improving students’ skill in writing descriptive texts using Brainstorming Technique. The objectives were: 1) To find out whether the use of Brainstorming Technique can improved the writing skill in descriptive texts of tenth grade students of SMK Plus Bhakti Oetama Gondangrejo in the academic year of 2017/2018, and   2)   To   d e s c r i b e   t h e   c l a s s   c o n d i t i o n   w h e n   brainstorming  technique  were implemented in writing skill in descriptive texts of tenth grade students of SMK Plus Bhakti Oetama Gondangrejo in the academic year of 2017/2018. The researcher wa s  conducted in c l a s s  X  wh i c h  c o n s i s t e d  o f  3 0  f e ma l e  s t u d e n t s  from August to September 2017. This Classroom  Action  Research  (CAR)  consisted  of  2  cycles.  Each  cycle  consisted  of  two meetings in 80 minutes for each meeting. The data were collected through test and non-test. The tests consisted of pre-test and post-tests. While, non-tests consisted of observation, interview, field notes and documentation.  Furthermore,  the  researcher  used  qualitative  and quantitative   data analysis to analyze the data. The result of this research showed that Brainstorming Technique could improve the students’ skill  in writing descriptive  texts  at  the tenth  grade  students  especially  class  X  of  SMK Plus Bhakti Oetama Gondangrejo.  The improvement could be seen from the result of the test. The mean score of pre-test was 4.80, post-test 1 was 6.93, and post-test 2 was 7.68. Moreover, the result of t-test was 12.321 in cycle 1 and 3.425 in cycle 2. It meant that there was improvement in students’ skill in writing descriptive texts. Key  words:  Writing  Skill;  Descriptive  Texts;  Brainstorming Technique; Classroom ActionResearch